A supramolecular polymer hybrid membrane with superior photothermal properties for local heating applications. (20th January 2021) - Li, Jie; Zou, Shufen; Deng, Cong; Na, Bing; Zhang, Shuang; Lin, Shan; Wang, Bin
Abstract: The challenge for photothermal membranes based on polymer composites is to achieve a high temperature at a low irradiation density. To this end, polydopamine modified graphene oxide nanosheets have been synthesized to act a highly efficient photothermal filler. The temperature of hybrid membranes with a supramolecular polymer as the matrix can reach 89.1 °C at a low irradiation density of 0.1 W/cm 2, superior to that of other polymer photothermal composites. Moreover, high softness and adhesiveness are exhibited by hybrid membranes, enabling easy attachment to other substrates without any aids. These merits assure local heating applications of hybrid membranes in photothermal therapy and thermoelectric generators. Graphical abstract: Image 1 Highlights: PDA modified GO is synthesized as a high-performance photothermal filler. A supramolecular polymer is the matrix with high softness and adhesiveness. Hybrid membrane can reach 89.1 °C at a low irradiation density of 0.1 W/cm 2 . Hybrid membrane is applied in photothermal therapy and thermoelectric generator.